Occupational Health of PT. Indonesian Ship Industry in Makassar City - S, Muh Rizal; Zainal, Henni (KnE Social Sciences, 2024)
Occupational health is an endeavor to keep employees healthy while they work and to protect them by providing health insurance while they labor. The goal of this study is to look at the occupational health of personnel at PT Indonesian Ship Industry (Persero) in Makassar City. A quantitative technique approach was applied in the investigation. This quantitative strategy is carried out by processing all of the data from the research instrument, through a questionnaire, which is then analyzed statistically. According to the findings of this study, the occupational health variable has a marginally significant influence on the job productivity of PT. Indonesian Ship Industry (Persero) Makassar City personnel. This is evident from the findings of the partial test (t-test) conducted in this study. Keywords: occupational health, employees, PT. Indonesian Ship Industry